2012
DOI: 10.1016/j.gsf.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for three types of mafic dyke swarms

Abstract: This study proposes three models to explain the mechanism of the three major types of mafic dyke swarms. Parallel dyke swarms form in response to a regional stress field, e.g. the mafic dyke swarms in the North China Craton, whereas small radiating dyke swarm forms due to stress constructions around a plutonic or volcanic edifice, such as the dyke swarm at Spanish Peak, USA. The third type of radiating dyke swarm is giant fan-shaped dyke swarm such as the Mackenzie dyke swarm. Fractures that formed prior to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 26 publications
0
33
0
2
Order By: Relevance
“…Giant radiating dyke swarms have been frequently related to mantle plume activities, typically linked with the breakup of the supercontinents (Ernst et al, 2013;Hou, 2012;Goldberg, 2010;Zhang et al, 2009;Ernst et al, 2008Ernst et al, , 1995Peng et al, 2007;Mayborn and Lesher, 2004;Ernst and Buchan, 2001a;Park et al, 1995). Smaller scale metamafic dyke swarms can be related to volcanic edifices in subduction settings, in back-arc environments or as one component of oceanic crustal complex (Peng et al, 2007;Ernst et al, 1995).…”
Section: Tectonic Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Giant radiating dyke swarms have been frequently related to mantle plume activities, typically linked with the breakup of the supercontinents (Ernst et al, 2013;Hou, 2012;Goldberg, 2010;Zhang et al, 2009;Ernst et al, 2008Ernst et al, , 1995Peng et al, 2007;Mayborn and Lesher, 2004;Ernst and Buchan, 2001a;Park et al, 1995). Smaller scale metamafic dyke swarms can be related to volcanic edifices in subduction settings, in back-arc environments or as one component of oceanic crustal complex (Peng et al, 2007;Ernst et al, 1995).…”
Section: Tectonic Settingsmentioning
confidence: 99%
“…Recently, Liao et al (2014) reported metamafic dyke swarms that intruded into the east Delingha region in the central east portion of the Quanji massif at ~1.85-1.83 Ma (Lu et al, 2008). Their study revealed that these dyke swarms have small-scale outcrops and limited distribution, and thus they cannot be regarded as giant mafic dike-swarms that are usually related to continental rifting or breakup of the supercontinents (Liao et al, 2014;Ernst et al, 2013Ernst et al, , 2008Ernst et al, , 1995Hou, 2012;Goldberg, 2010;Zhang et al, 2009;Peng et al, 2007;Mayborn and Lesher, 2004;Ernst and Buchan, 2001a). Combination of the affinity of backarc settings for their precursor magma at ~1.85-1.83 Ga and the medium-P/T type metamorphism of the dyke swarms at ~1.82 Ga (Chen et al, 2013a), Liao et al (2014) firstly proposed that an oceanic subduction process was going on before ~1.85 Ga. Our study reveals that the metamafic dykes within the paragneiss suite in the Delingha region carry even stronger signature of subduction-related volcanic arc setting, thus indicative of an oceanic lithosphere subduction process for generation of their precursor magma.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kusky and Santosh, 2009;Rogers and Santosh, 2009;Santosh et al, 2009a,b,c;Santosh, 2010b;Santosh et al, 2010;Meng et al, 2011;N. Li et al, 2011;Yang et al, 2011;Zhai and Santosh, 2011;Zhao et al, 2011;Hou, 2012;Deng et al, 2013) (Figs. 1 and 2).…”
mentioning
confidence: 99%
“…Zhang et al, 2007;Xu et al, 2007;Wang et al, 2007aWang et al, ,b, 2008He et al, 2008;Hou et al, 2008a,b;Peng et al, 2008;He et al, 2009;T.P. Zhao et al, 2009;He et al, 2010a,b;Peng, 2010;Wang et al, 2010;Cui et al, 2011;Hou, 2012).…”
unclassified